The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2333794x20961575
|View full text |Cite
|
Sign up to set email alerts
|

Perception that Mothers and / or Guardians of Overweight or Obese Preschool Children Have of a Text Messaging Program to Support Behaviour Change in their Children

Abstract: In most childhood obesity preventive programs, parents are targeted as they are key in achieving lifestyle behavior change in their children. Because their participation is generally low, new technologies, such as text messaging, are being tested to assess if their participation increases. The objective of this study was to determine the perception that mothers of overweight/ obese preschool children have of a textmessaging program developed to support their children’s lifestyle behavior change. Text messages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Parra-Soto et al 29 conducted a mixed-methods, quasi-experimental, and qualitative study to examine mothers' opinions of receiving WhatsApp text messages encouraging healthy food and physical activities for their overweight/obese preschoolers. Mothers viewed text messages as a means of support for ensuring that positive behaviors were practiced in order to promote healthier lifestyles for their children 29 . Likewise, one-way text messages were sent to parents of children with ADHD using WhatsApp messenger to help them improve their child's behavior 28 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Parra-Soto et al 29 conducted a mixed-methods, quasi-experimental, and qualitative study to examine mothers' opinions of receiving WhatsApp text messages encouraging healthy food and physical activities for their overweight/obese preschoolers. Mothers viewed text messages as a means of support for ensuring that positive behaviors were practiced in order to promote healthier lifestyles for their children 29 . Likewise, one-way text messages were sent to parents of children with ADHD using WhatsApp messenger to help them improve their child's behavior 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Over half of studies (56.25%) consistently indicated that parents perceived texting as useful for disease management. 24,25,[29][30][31][32]35,37,38 Among the studies reviewed, 56.25% examined the effectiveness of text message-based interventions on child health outcomes. Several studies 24,25,33,34,36,39 showed that text messaging was effective for child health outcome variables such as generic-and sickle cell-specific child HrQL, vaccine reception, clinic attendance, BMI, duration of physical activity and sedentary behavior, missed vaccination opportunity, and asthma symptom-free days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations